Asymmetric transfer hydrogenation of imines in water/methanol co-solvent system and mechanistic investigation by DFT study - Shende, Vaishali S.; Shingote, Savita K.; Deshpande, Sudhindra H.; Kuriakose, Nishamol; Vanka, Kumar; Kelkar, Ashutosh A. (RSC Advances, 2014)
Asymmetric transfer hydrogenation of various cyclic imines proceeded efficiently with water/methanol co-solvent media in 20 min with excellent yields and enantioselectivities by employing Rh-TsDPEN catalyst and sodium formate as a hydrogen donor. The role of the co-solvent in enhanced productivity of the reaction was investigated by DFT. The mechanism for ATH of the imines has been discussed on the basis of the DFT study.

Asymmetric transfer hydrogenation of imines in water by varying the ratio of formic acid to triethylamine - Shende, Vaishali S.; Deshpande, Sudhindra H.; Shingote, Savita K.; Joseph, Anu; Kelkar, Ashutosh A. (Organic Letters, 2015)
Asymmetric transfer hydrogenation (ATH) of imines has been performed with variation in formic acid (F) and triethylamine (T) molar ratios in water. The F/T ratio is shown to affect both the reduction rate and enantioselectivity, with the optimum ratio being 1.1 in the ATH of imines with the Rh-(1S,2S)-TsDPEN catalyst. Use of methanol as a cosolvent enhanced reduction activity. A variety of imine substrates have been reduced, affording high yields (94-98%) and good to excellent enantioselectivities (89-98%). In comparison with the common azeotropic F-T system, the reduction with 1.1/1 F/T is faster.

Rhodium complex with unsymmetrical vicinal diamine ligand: excellent catalyst for asymmetric transfer hydrogenation of ketones - Deshpande, Sudhindra H.; Shende, Vaishali S.; Shingote, Savita K.; Chakravarty, Debamitra K.; Puranik, Vedavati G.; Chaudhari, Raghunath V.; Kelkar, Ashutosh A. (RSC Advances, 2015)
New unsymmetrical vicinal diamine ligands with systematic variation in the regio and stereo positions in the amine and sulphonamide groups were synthesized from cheap starting material such as norephedrine. Catalytic Asymmetric Transfer Hydrogenation (ATH) of aromatic alkyl ketones has been investigated using transition metal complexes and new derivatives of monotosylated unsymmetrical vicinal diamine ligands using sodium formate as the hydrogen source, in water and methanol. Chiral secondary alcohols were obtained with excellent enantioselectivity (>95% ee) and conversion of ketones (>95%) with [Rh(Cp*)Cl-2](2) and ligand 4 as a catalyst. Enantioselectivity was found to be slightly higher with the use of methanol as a solvent for ATH of ketones with sodium formate as the hydrogen source compared to water as a solvent and was found to be consistent with all the ketones investigated. The reaction mixture is homogeneous in methanol unlike in water, where substrate and product are insoluble in water and form separate phase, sodium formate being soluble in water. The activity and enantioselectivity obtained for ATH of ketones using [Rh(Cp*)Cl-2](2) and unsymmetrical vicinal diamine ligand as catalyst was comparable with the C2 symmetric benchmark ligands like TsDPEN ((1R, 2R)-N-(p-tolylsulfonyl)-1,2-diphenylethylene- diamine), and TsCYDN ((1R, 2R)-N-(p-tolylsulfonyl)-1,2-cyclohexyl, diamine) under similar reaction conditions. To the best of our knowledge, this is first example of the ATH of ketones with good activity and high enantioselectivity with [Rh(Cp*)Cl-2](2) and unsymmetrical vicinal diamine ligands as catalyst systems.

Asymmetric transfer hydrogenation of cyclic imines in water with a versatile hydrogen donorformic acid/N-methylpiperidine: rapid access to highly enantioselective amines - Shende, Vaishali S.; Shingote, Savita K.; Deshpande, Sudhindra H.; Kelkar, Ashutosh. A. (Chemistryselect, 2016)
Asymmetric transfer hydrogenation (ATH) of cyclic imines in water has been investigated for the first time by using HCOOH in combination with bases other than triethylamine as H donor. Effect of FA/Base ratio has shown significant impact on activity and enantioselectivity for ATH reaction in water. Use of methanol as a co-solvent improved the reduction performance. FA/N-methylpiperidine was found to be excellent, versatile hydrogen donor for ATH of imine 6,7-dimethoxy-1-methyl-3,4-dihy-droisoquinoline (1a) giving by far the highest noted TOF value of 5940 h(-1). ATH of-different imines derivatives including 3, 4-dihydoisoquinolines, beta-carbolines and cyclic sulfonyl imines have been performed with excellent activity (91-99% yield) and enantioselectivity (88-97%) in very short time (1-2 min). This is very simple protocol for rapid access to enantioselective amines with very new and versatile hydrogen donor 1.1 FA/Nmethylpiperidine.

Room-temperature asymmetric transfer hydrogenation of biomass-derived levulinic acid to optically pure gamma-valerolactone using a ruthenium catalyst - Shende, Vaishali S.; Raut, Amol B.; Raghav, Prathamesh; Kelkar, Ashutosh A.; Bhanage, Bhalchandra M. (ACS Omega, 2019)
This study presents a first report on ruthenium-catalyzed asymmetric transfer hydrogenation (ATH) of levulinic acid (LA) to chiral gamma-valerolactone (GVL). ATH of LA has been explored with Noyori's chiral catalyst (Ru-TsDPEN) in methanol solvent. Efficacy of ATH reaction of LA was investigated under different reactions conditions such as temperature, catalyst, and hydrogen donor concentration. The effect of various organic tertiary bases along with formic acid (FA) as a hydrogen donor was studied, and N-methylpiperidine with FA (1:1 molar ratio) was revealed as an efficient hydrogen donor for ATH of LA to GVL furnishing chiral GVL with complete conversion and 93% enantiomeric excess (ee). This operationally simple and mild ATH protocol was tested for practical applicability of ATH of LA obtained from biomass waste (rice husk and wheat straw) and furnished chiral GVL with 82% ee.